Sprinting in a Marathon: Nursing Staff and Nurse Leaders Make Meaning of Practicing in COVID-19 Devoted Units Pre-Vaccine - Natalie S. McAndrew PhD, RN, ACNS-BC; William E. Rosa PhD, MBE, NP-BC, FAAN, FAANP; Kaylen M. Moore BSN, RN, CCRN, SANE-A; Jacqueline Christianson MSN, RN, FNP-C; Tala AbuZahra BSN, RN; Megann Mussatti DNP, APRN; Colleen McCracken MSN, RN, CMSRN, CHPN, OCN; Amy R. Newman PhD, RN, CPNP-PC; Kelly Calkins PhD, RN; Susan Breakwell DNP, PHNA-BC, FPCN; Katie Klink PhD, RN, CNL; Jill Guttormson PhD, RN (SAGE Publishing, 2023)
Objective To describe the lived experience of nursing staff and nurse leaders working in COVID-19 devoted units (intensive care or medical unit) prior to vaccine availability. Research Design Qualitative phenomenological design with a focus group approach. Methods The study team recruited a convenience sample of nursing staff (nurses, and nursing assistants/nurse technicians) and nurse leaders (managers, assistant nurse managers, clinical nurse specialists, and nurse educators) at an academic medical center in the midwestern United States. Focus groups and individual interviews were conducted to encourage participants to describe their (1) experiences as nursing professionals, (2) coping strategies, and (3) perspectives about supportive resources. Moral distress was measured with the moral distress thermometer and qualitative data were analyzed with Giorgi-style phenomenology. Results We conducted 10 in-person focus groups and five one-on-one interviews ( n   =  44). Seven themes emerged: (1) the reality of COVID-19: we are sprinting in a marathon; (2) acute/critical care nurse leaders experience unique burdens; (3) acute/critical care staff nurses experience unique burdens; (4) meaning of our lived experience; (5) what helped us during the pandemic; (6) what hurt us during the pandemic; and (7) we are not okay. Participants reported a moderate level of moral distress ( M   =  5.26 SD   =  2.31). They emphasized that peer support was preferred over other types of support offered by the healthcare organization. Participants expressed positive feedback about the focus group experience and commented that group processing validated their experiences and helped them "feel heard." Conclusion These findings affirm the need for trauma-informed care and grief support for nurses, interventions that increase meaning in work, and efforts to enhance primary palliative communication skills. Study findings can inform efforts to tailor existing interventions and develop new, more comprehensive resources to meet the psychosocial needs of nursing staff and nurse leaders practicing during a pandemic.